2020
DOI: 10.1021/acs.jpca.0c00286
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Theoretical Studies on Planar Chirality of Partially Overlapped C2-Symmetric [3.3](3,9)Dicarbazolophanes

Abstract: Partially overlapped dicarbazolophanes exhibit a planar chirality. In this study, C 2 -symmetrical [3.3](3,9)dicarbazolophane derivatives (CZ1−CZ3) have been optically resolved by preparative chiral high-performance liquid chromatography for the first time. In their circular dichroism (CD) spectra, moderate Cotton effects (CEs) were observed for their 1 L b and 1 L a transitions (|Δε| = 10−12 and 51−57 M −1 cm −1 , respectively), while intense CEs were notified in their 1 B transitions (|Δε| = 156−216 M −1 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…The corresponding g CD and g CPL factor values were on the order of 10 –3 and were more than doubled compared to those of the component [6]­helicene. The time-dependent second-order approximate coupled-cluster singles and doubles model using the resolution-of-the-identity method (RI-CC2) was employed to theoretically elucidate the electric ( μ ) and magnetic ( m ) dipole transition momental origins of such an unusual chiroptical response enhancement. It was found that, in the 1 B b band region, the relevant μ and m vectors are aligned in the same direction for both of the double helicenes, while the angle is 70° in the component [6]­helicene.…”
Section: Double Carbohelicenesmentioning
confidence: 99%
“…The corresponding g CD and g CPL factor values were on the order of 10 –3 and were more than doubled compared to those of the component [6]­helicene. The time-dependent second-order approximate coupled-cluster singles and doubles model using the resolution-of-the-identity method (RI-CC2) was employed to theoretically elucidate the electric ( μ ) and magnetic ( m ) dipole transition momental origins of such an unusual chiroptical response enhancement. It was found that, in the 1 B b band region, the relevant μ and m vectors are aligned in the same direction for both of the double helicenes, while the angle is 70° in the component [6]­helicene.…”
Section: Double Carbohelicenesmentioning
confidence: 99%
“… 2 To develop CPL dyes, connecting two of the same aromatic luminophores, which can form an excimer (excited homodimer), to a chiral unit is one of the main approaches because these luminophores often emit with high quantum yields and large Stokes shifts. For example, CPL-active pyrene, 3,4 perylene, 4 b ,5 anthracene, 6 carbazole, 7 and naphthalimide 5 c ,8 excimers have been reported. In contrast, exciplex (excited heterodimer) CPL dyes are still rare, although exciplex fluorescence (FL) dyes are often used in the field of materials and biological sciences.…”
Section: Introductionmentioning
confidence: 99%
“…A simultaneous introduction of electron‐withdrawing and ‐donating functions to [7] helicene was found to significantly enhance its CPL features, which was ascribed to a proper control of the relevant molecular orbitals [24a] . In chiral carbazolophanes, the relative geometries of two carbazole moieties were recently shown to impact on the chiroptical responses and excimer emission in particular [24b] …”
Section: Methodsmentioning
confidence: 99%